PENGARUH PENDIDIKAN KESEHATAN TENTANG MENSTRUASI TERHADAP KESIAPAN REMAJA PUTRI DALAM MENGHADAPI MENARCH PADA SISWI DI SD GMIH DUONO WILAYAH KECAMATAN IBU UTARA - Karlina Miringit, Alfiani; Maulina, Rifzul (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Elementary school students experiencing their first menstruation are confused and not ready to face menarche and Schools in remote villages and lack of exposure to information are one of the factors Many of her students do not know about Menarche. The purpose of the study is known The Influence of Health Education on Readiness to Face Menarche in Elementary School Students. The type of research is pre-experiment with a design model of one pretest-protest group. Sampling technique with Purposive Sampling. The sample was 15 students. Data analysis with paired t test. Average knowledge of menarche before education is 7.27 and after education is carried out 10.47. Average readiness before menarche is 4.13 and After 7.00 facing menarche students. There is an influence of health education on Student Knowledge of Knowledge and Readiness to Face Students. There is an influence of education health to readiness to face Menarche in elementary school students It is hoped that there will be socialization or learning about readiness to face menarche to elementary school students and the community.